PENGARUH KREDIT MACET TERHADAP PENDAPATAN BANK PT BPR BANDUNG KIDUL PERIODE TAHUN 2012-2016 - KOMARUDIN; MUTIA RAHAYU GUMULYA MUTIA RAHAYU GUMULYA (POLITEKNIK PIKSI GANESHA, 2019)
This research aimed to know the influence of non performing loan to the revenue at PT BPR Bandung Kidul the periode 2012-2016. The type of this research is method quantitative descriptive analysis. The technique of analysis data was used Test Data Normality method, the correlation analysis of pearson product moment, analysis simple linier regression relations , coefficient of determinations, and T-test. The technique of collecting data used observation, interview, and literature study. The result showed a very strong and positive relationship with a correlation coefficient of 0,883 or 88,3% Meanwhile, the coefficient of determination 0,780 or 78%, meaning that is the non performing loan contributed 78% to income . T-test showed a significant influence was shown by tcount = 3,528 > ttable = 2,353. The Suggestions of this research is in the settlement of problem loans, it is suggested that good cooperation between the customer, bank and third party that assist in settling the non performing loans.